Agents in Balinese passive construction - Sujaya, Nyoman; Winaya, Made Detrichyeni; Sukiani, Ni Ketut (Linguistics and Culture Review, 2021)
This paper accounts for the agents in Balinese passive forms. It focuses on kinds of agent and their syntactic and semantic representation in Balinese passive constructions. This research used two novels, namely Dadi Ati written by Manda (2013) and Ki Baru Gajah by Sugianto (2015) as the data source. To support the data, this research also used informants. Aplying the RRG theory proposed by Van Valin and Randy (1999) and ideas from Balinese experts, it was found out that the agents of Balinese passive sentences varied in their forms and applied various constructions and semantic representation. Some constructions of passive sentences do not have an agent in their usage and some do have it. The ka- passive forms, for example, generally have no agents, but the ka- forms followed by suffix -ang or -in do need an agent. The first and second person agents directly follow the verb in the passive constructions. These two agents may be expressed by a noun. The pronoun in the third person as an agent can be expressed by suffix -a. Frequently the agents are expressed by a prepositional phrase.